The dipeptidyl peptidase-4 inhibitor teneligliptin reduces kidney damage from hypercholesterolemia in apolipoprotein E-deficient mice. Issue 14 (27th January 2017) - Liu, Hui; Li, Nan; Liu, Ying; Xing, Jing; Feng, Shuai; Li, Mengye; Liu, Jinping; Gao, Huiling; Lu, Yan; Liu, Hongyang
Abstract : Hypercholesterolemia is a well-established risk factor for kidney injury that can lead to chronic kidney disease (CKD). Abstract : Hypercholesterolemia is a well-established risk factor for kidney injury that can lead to chronic kidney disease (CKD). Many clinic data show that dipeptidyl peptidase-4 (DPP-4) inhibitor is protective against kidney damage in diabetes patients. The goal of this study was to investigate the possible protective effects of teneligliptin against kidney injury in apolipoprotein E knockout (ApoE −/− ) mice. Eight-week-old male ApoE −/− mice were randomly divided into the following 3 groups: a control group fed a normal diet (ND group), a group fed a high cholesterol diet (HD group) or a group fed HD mixed with teneligliptin (HD + Tene group). All groups received different treatments for 6 weeks. The metabolic characteristics of total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-c) and creatinine (Cre) were lower in ApoE −/− HD + Tene mice than ApoE −/− HD mice. Oil-red O staining revealed excessive lipid deposition in the kidneys of ApoE −/− HD mice; however, it was significantly suppressed in the ApoE −/− HD + Tene mice. Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) gene and protein expression was lower in the kidney tissue of ApoE −/− HD + Tene mice than ApoE −/− HD mice. These results indicate that teneligliptin may provide a potential therapeutic target for kidney damage from hypercholesterolemia.